A case of Schamberg's disease responding dramatically to PUVA treatment - SEÇKİN GENÇOSMANOĞLU, DİLEK (WILEY, 2008)
Pigmented purpuric dermatoses are a group of chronic, recurrent disorders characterized by purpuric lesions mainly involving the lower extremities. Their etiology is unknown. Treatment options are limited and none of them have proven benefit. Phototherapy has been reported to be effective in a small number of patients in the literature. We present a case of Schamberg's disease showing a dramatic response to psoralen plus ultraviolet A therapy and discuss the current therapeutic options focusing mainly on phototherapy. We believe that phototherapy is a valuable alternative, especially for patients with long-standing and widespread pigmented purpuric dermatitis.
Keywords: pigmented purpuric dermatitis; PUVA; Schamberg; PURPURIC LICHENOID DERMATITIS